Ganglioneuroma of mediastinum and adrenal gland - Bui Binh Bao Son; Nguyen Thi Kim Hoa; Carlos Rodriguez- Galindo (Elsevier, 2020)
Introduction: Ganglioneuroma is a rare benign nervous tumor arising from sympathetic ganglion which commonly occurs at posterior mediastinum, retroperitoneum and adrenal gland. Case: We report a 6 year-old boy who presented with abdominal pain. CT scan and MRI showed one tumor at his right posterior mediastinum area measuring 8.3 × 6.3 × 5.3cm, and the other tumor at his right adrenal gland measuring 3.9 × 3.4 × 3.2 cm. A biopsy showed ganglioneuroma, and complete resection of both tumors was performed. Post operative biopsy confirmed definitive diagnosis as ganglioneuroma. The patient is well after surgery. Conclusion: Ganglioneuroma is benign and treatment is complete surgical resection. Prognosis after surgical resection seems to be so good, without any recurrences or need for adjunct therapy.